ANALYSIS OF ANTIBODY STATUS OF BALI CATTLE BEFORE AND AFTER FOOT AND MOUTH DISEASE (FMD) VACCINATION IN RENDANG VILLAGE, KARANGASEM - Lubis, Shakila; Sulabda, I Nyoman; Sari, Tri Komala (Buletin Veteriner Udayana, 2026)
Bali cattle (Bos sondaicus) are an indigenous cattle breed originating from Indonesia and widely distributed across various regions of Indonesia. However, in 2022, the population declined due to an outbreak of Foot and Mouth Disease (FMD). The main strategy to control FMD is through vaccination, and the effectiveness of vaccination can be evaluated by detecting the presence of antibodies using serological tests, such as Enzyme-Linked Immunosorbent Assay (ELISA). This study aimed to analyze the difference in antibody status in Bali cattle before and after FMD vaccination using a competitive ELISA test. The samples were divided into two groups of male Bali cattle calves aged under one year. The first group was seronegative calves (n=12), and the second group was seropositive calves (n=7) based on the pre-vaccination ELISA test. Data were analyzed using the McNemar test and Paired t-test after the data were confirmed to be normally distributed (Shapiro-Wilk, P > 0.05). The statistical results showed that in the first group, there was no significant difference (P > 0.05) in antibody status before and after vaccination. In contrast, a significant difference (P < 0.05) in antibody levels was found in the second group before and after vaccination. These findings indicate that vaccination in the first group was not fully capable of triggering the desired immune response, while in the second group, booster vaccination could maintain and enhance the existing immune response. Therefore, it is recommended to implement the existing vaccination protocol and conduct accurate data collection regarding livestock vaccination status.